2017
DOI: 10.1037/ocp0000042
|View full text |Cite
|
Sign up to set email alerts
|

Drawbacks of proactivity: Effects of daily proactivity on daily salivary cortisol and subjective well-being.

Abstract: The benefit of proactive work behaviors for performance-related outcomes has been well established. However, this approach to studying proactivity has not yet acknowledged its potential implications for the actor's well-being. Drawing on the fact that resources at work are limited and that the workplace is a social system characterized by interdependencies, we proposed that daily proactivity could have a negative effect on daily well-being. We furthermore proposed that this effect should be mediated by work ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
100
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(105 citation statements)
references
References 76 publications
(106 reference statements)
2
100
3
Order By: Relevance
“…In line with this, research has suggested that engaging in proactivity is associated with increased strain. Whereas Fay and Hüttges () studied end‐of‐day fatigue as a consequence of proactivity, Strauss et al . () found that supervisor‐reported proactivity was positively related to employees’ affective strain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this, research has suggested that engaging in proactivity is associated with increased strain. Whereas Fay and Hüttges () studied end‐of‐day fatigue as a consequence of proactivity, Strauss et al . () found that supervisor‐reported proactivity was positively related to employees’ affective strain.…”
Section: Introductionmentioning
confidence: 99%
“…Our second contribution relates to the nature of strain. Previous research on well‐being outcomes of proactivity has largely focused on a limited number of well‐being indicators (e.g., affect‐related: Strauss et al ., ; Zacher et al ., ; physiological indicators of strain: Fay & Hüttges, ; or ego depletion: Lin & Johnson, ). The present study continues this stream of research by including irritability as an indicator of affect‐related strain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time pressure has – in theory – been discussed both as a facilitator and as a consequence of PWB (e.g., Frese & Fay, ). While several studies have investigated time pressure as a potential facilitator of PWB (e.g., Fritz & Sonnentag, ; Ohly & Fritz, ; Prem, Paškvan, Kubicek, & Korunka, ), research that investigates time pressure as a consequence of PWB is scarce (i.e., Fay & Hüttges, , who investigated daily work overload). We address this research gap and propose that PWB – due to its resource‐consuming nature – is positively related to experiencing subsequent time pressure.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it has also been acknowledged that behaving proactively is likely to consume resources by itself, first and foremost time and energy (e.g., Bolino et al ., ; Ng & Feldman, ). Accordingly, first empirical studies show that PWB is associated with higher levels of job strain (Strauss et al ., ), emotional exhaustion (Pingel et al ., ; Zacher et al ., ), and daily cortisol levels (Fay & Hüttges, ). In line with these results, we propose that showing PWBs may actually contribute to experiencing higher levels of stressors at work.…”
Section: Introductionmentioning
confidence: 99%